Anti-corrosion behaviour of VE/GF coatings on mild steel - Barbhuiya, Salim; Choudhury, I.; Memon, S. (Carl Hanser Verlag, 2014)
In this study, the properties of vinyl ester/glass flake (VE/GF) coating on mild steel plates was investigated to determine its anti-corrosion performance. The corrosion penetration rate of VE/GF coated and uncoated mild steel was evaluated using immersion tests for 20 days. Corrosion resistance of the coating was evaluated in various corrosive environments viz. 5% HCl, 8% HCl, 5% NaOH and 7% NaOH. The mild steel plates were coated with four different thicknesses of VE/GF coating and a comparative analysis was carried out to evaluate the corrosion protection efficiency. Scanning electron microscopy was carried out before and after the immersion test to study the morphological changes and products of corrosion.